Begegnungen mit China. - Becker, Wolfgang; Joch, Peter; Kotzenberg, Heike; Lagler, Annette; Pechinger, Evelyn (Aachen : Ludwig Forum für Internationale Kunst, 1996)
Fang Lijun ; Guan, Gu ; Hong, Yu ; Huang Yong Ping ; Jingsong, Wang ; Miaozi, Huang ; Ping, Su Xin ; Reng, Li Hong ; Rong, Zhou Ji ; Sheng, Gao Rong ; Siao, Eva ; Wang Guangyi ; Ai Weiwei ; Wendu, Ji ; Youhan, Yu
Begegnungen mit China, Ludwig Forum für Internationale Kunst, Aachen, März - Oktober 1996
Duits
kunstcatalogus
Keywords: China